The antimicrobial activity of bupivacaine, lidocaine and mepivacaine against equine pathogens: An investigation of 40 bacterial isolates. (May 2017) - Adler, D.M.T.; Damborg, P.; Verwilghen, D.R.
Highlights: Local anaesthetics present in vitro antimicrobial activity against common equine pathogens. Local anaesthetics have antimicrobial activity against both Gram-positive and Gram-negative bacteria. Lidocaine has the most potent antimicrobial effect followed by bupivacaine and mepivacaine. The antimicrobial effect questions the need for routine prophylactic antibiotics during diagnostic analgesia in horses. Abstract: Lameness is the most commonly reported health problem in horses, and lameness investigations which include local anaesthetic injections are routinely performed by equine practitioners. Through this process, bacteria can enter the tissues perforated by the needle and may cause local infections at the injection site. The objective of this in vitro study was to investigate if local anaesthetics at concentrations available in commercially available solutions could inhibit growth and/or kill bacteria that could be inoculated into the synovial space or soft tissues during injection. This study evaluated the antimicrobial activity of the local anaesthetics bupivacaine, lidocaine and mepivacaine against 40 equine clinical bacterial isolates of the Actinobacillus, Corynebacterium, Enterobacter, Escherichia, Pseudomonas, Rhodococcus, Staphylococcus and Streptococcus genera. Minimum inhibitory and minimum bactericidal concentrations (MICs and MBCs) were determined by the broth microdilution method. Clinically applied concentrations of bupivacaine, lidocaine, and mepivacaine inhibited visual growth of 93%, 93%, and 80% of isolates tested, respectively. For the majority (80%) of the inhibited isolates, the concentrations were also bactericidal. The tested local anaesthetics possessed antimicrobial activity against equine pathogens at concentrations that are routinely applied in clinical cases. However, this antimicrobial activity should not discourage antiseptic preparation prior to local anaesthetic injections.